Crustacean and mollusk species diversity and abundance in the mangrove communities of Mimika District, Papua, Indonesia - Gesang Setyadi; DWI LISTYO Rahayu; Rudhi Pribadi; RETNO HARTATI; DIAH PERMATA Wijayanti; DENNY NUGROHO Sugianto; Agung Darmawan (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Setyadi G, Rahayu DL, Pribadi R, Hartati R, Wijayanti DP, Sugianto DN, Darmawan A. 2021. Crustacean and mollusk species diversity and abundance in the mangrove communities of Mimika District, Papua, Indonesia. Biodiversitas 22: 4146-4157. A mangrove crustacean and mollusk species diversity study was carried out in four mangrove estuaries in Mimika District, Papua, Indonesia. Two locations were selected on each estuary; for each location, samples of crustaceans and mollusks were collected from 5 m × 5 m plots, and mangrove trees were recorded on 10 m × 10 m plots at a distance of 10 m, 250 m and 500 m perpendicular to the riverbank. This study recorded a total of 41 species of crustaceans and 32 species of mollusks the latter comprising three species of bivalves and 29 gastropod species. The number of crab species found was among the highest compared to similar studies in the world. The average number of species collected from each 25 m2 plot was 7.6 ± 4.2 species for crustaceans, with an average abundance of 87 ± 3.5 individuals; for mollusks, it was 3.3 ± 3 species with an average abundance of 28 ± 48.4. Crustacean abundance and species composition were influenced by inundation frequency. There was a strong correlation between the crab Parasesarma cricotum and the association of Rhizophora apiculata and Bruguiera gymnorrhiza mangroves, and Clistocoeloma amamaparense and the association of B. gymnorrhiza, R. apiculata, and Bruguiera parviflora mangroves. For mollusks, correlations were found between Terebralia palustris and Ellobium aurisjudae and the association of R. apiculata and B. parviflora mangroves. The highest crustacean Shannon-Wiener diversity index was associated with Sonneratia alba and Avicennia marina mangroves, and the highest mollusk Shannon-Wiener diversity index was associated with R. apiculata and B. gymnorrhiza mangroves.